Phenol degradation and molecular analysis of phenol hydroxylase from Acinetobacter sp. - Mohamad Rashid, Muhamad Syirhan Akmal (2015)
Phenol is the simplest member of a family of compounds in which an -OH group is attached directly to a benzene ring, can be found either naturally or man-made. Phenol are classified as highly hazardous chemical due to their toxic, mutagenic, and carcinogenic characteristic. Bioremediation was chosen to solved the phenol pollution due to environmental friendly, rapid and cost effective. Acinetobacter sp. is one of the bacteria that can degrade phenol. The key enzyme for the degradation of phenol in Acinetobacter sp. is phenol hydroxylase. The highest degradation rate of phenol by Acinetobacter sp. is 3.57 mg/h at concentration 600 mg of phenol. The molecular analyse result confirmed the presence of phenol hydroxylase in Acinetobacter sp.